2010
DOI: 10.1016/j.cub.2009.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Dopamine in Circadian Rhythmicity and Extreme Light Sensitivity of Circadian Entrainment

Abstract: Summary Light has profound behavioral effects on almost all animals, and nocturnal animals show sensitivity to extremely low light levels [1–4]. Crepuscular, i.e., dawn/dusk-active animals such as Drosophila melanogaster are thought to show far less sensitivity to light [5–8]. Here we report that Drosophila respond to extremely low levels of monochromatic blue light. Light levels 3–4 orders of magnitude lower than previously believed impact circadian entrainment and the light-induced stimulation of locomotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 45 publications
(40 reference statements)
6
66
1
Order By: Relevance
“…The failure of a transgene expressing TH to rescue circadian rhythmicity in the TH-deficient pale mutant has been attributed to a hypothesized lack in the temporal cycling of the TH transcript (Hirsh et al 2010). Similarly, we cannot rule out the possibility that some of the circadian deficits we observed were caused by incomplete temporal regulation of DVMAT expression.…”
Section: Possible Cooperative Effects Between Aminergic Systemsmentioning
confidence: 80%
See 3 more Smart Citations
“…The failure of a transgene expressing TH to rescue circadian rhythmicity in the TH-deficient pale mutant has been attributed to a hypothesized lack in the temporal cycling of the TH transcript (Hirsh et al 2010). Similarly, we cannot rule out the possibility that some of the circadian deficits we observed were caused by incomplete temporal regulation of DVMAT expression.…”
Section: Possible Cooperative Effects Between Aminergic Systemsmentioning
confidence: 80%
“…An earlier study indicated that 5-HT is required for light input to the clock circuitry via the 5-HT1B receptor and glycogen synthase kinase 3b signaling (Yuan et al 2005). More recently, it has been shown that flies with reduced neural DA exhibit defects in circadian light sensitivity, circadian entrainment, and free-running rhythmicity [i.e., in DD after entrainment (Hirsh et al 2010)]. We find that dVMAT mutants lacking vesicular release of 5-HT, DA, and OA show decreased activity in the DAMS monitor (Figure S7A) and exhibit an altered profile of daily activity in LD.…”
Section: Possible Cooperative Effects Between Aminergic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…While many of these genes have only one or two shared same-direction outliers, two genes, Dopamine transporter (DAT) and RpS14b, stand out for containing four or more differentiated SNPs within relatively short genomic regions in the UTR and upstream regions (and therefore may be associated with regulation of expression). Dopamine is a neurotransmitter that has many biological roles, one of which is the circadian rhythm (Hirsh et al 2010), a clinally varying trait in D. melanogaster . A mutation in D. melanogaster DAT is associated with decreased sleep duration and arousal threshold (Kume et al 2005;Kume 2006), as well as metabolic rate and thermal preference and tolerance (Ueno et al 2012).…”
Section: Shared Differentiation At Snpsmentioning
confidence: 99%